The human mRNA decay machinery: an unexpected role for DIS3L2 over nonsense-mediated decay targets - da Costa, Paulo J. (2018)
Tese de doutoramento em Biologia (Biologia de Sistemas), apresentado à Faculdade de Ciências da Universidade de Lisboa, 2018